International Basic Safety Standards for Protection against Ionizing Radiation and for the Safety of Radiation Sources Safety series No. 115 - Zandberg, Jerzy (Contemporary Oncology/Współczesna Onkologia, 2000)
This article presents in a popular form the problems of radiation protection and of radiation protection quality assurance in a nuclear medicine facility wishing to comply with Polish and basic international standards for ionizing radiation protection.